Investigation of boris and ctcf genes expression by sybr-green based realtime rt-pcr in human brain tumors - Faizul Rahman, Sjafri (Universiti Sains Malaysia, 2008)
The major aim of this study is to study the BORIS and CTCF genes expression in brain tumors by determines the relative quantification of expression by Real-Time RT -PCR analyses. The result in this study is vital as one of other new approaches for the diagnostic or prognostic brain tumour purposes. To investigate the expression of these genes' m.RNA, the samples of total RNA was prepared for each tumour sample. Intact total RNA with purity between 1.8 - 2.0 was used for synthesis of eDNA. In order to confirm the expression level of BORIS and CTCF gene, gene-specific primer were designed using sequence obtained from GenBank (Primer Express Software version 2.0 Apllied Biosystem). Real-Time RT-PCR analysis was conducted by measuring the given level of fluorescence as the number of cycle threshold (Cr ). These Cr values serve as indirect indicators of gene expression so that samples with high expression of a given gene will exhibit lower Cr value than samples showing low level of gene expression. A gene is considered differentially expressed if its relative expression is two-fold or greater. In this study, the results of Real-Time RT-PCR demonstrated that the expression level of the CTCF was significantly higher in tumor than in normal in 2.8 fold. However, there was no BORIS expression was detected either in tumor or normal sample. Even though this is only preliminary study due to restricted number of samples and also limited time given, however, we believe that by further this study will guide us to appreciate better the role of BORIS and CTCF genes in formation of brain tumor.